THE EFFECT OF THE PROBING PROMPTING LEARNING MODEL ON THE CRITICAL THINKING ABILITY OF GRADE X STUDENTS IN HISTORY LEARNING AT SMK INFORMATICA CITY OF SERANG : Pengaruh Model Pembelajaran Probing Prompting terhadap Kemampuan Berpikir Kritis Siswa Kelas X Pada Pembelajaran Sejarah di SMK Informatika Kota Serang - Irma Wulandari; Arif Permana Putra; Agus Rustamana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the effect of the Probing–Prompting learning model on students’ critical thinking skills in history learning. A quantitative approach with a quasi-experimental design was employed. The population consisted of 188 tenth-grade students at a vocational high school in Indonesia. Using purposive sampling, two classes were selected as research samples: one experimental class applying the Probing–Prompting model and one control class applying the Discovery Learning model. Students’ critical thinking skills were measured using a multiple-choice test based on Ennis’s critical thinking indicators. Data were analyzed using descriptive statistics and independent sample t-tests. The results indicate that the experimental class achieved a higher mean post-test score (69,38) compared to the control class (51,36). The t-test results show a significance value of 0,000 (< 0,05), indicating a statistically significant difference between the two groups. These findings demonstrate that the Probing–Prompting learning model has a significant positive effect on students’ critical thinking skills in history learning. This study contributes to the development of student-centered instructional strategies that promote higher-order thinking skills in history education.